2018
DOI: 10.1080/14779072.2018.1534069
|View full text |Cite
|
Sign up to set email alerts
|

Optimal medical treatment of hypertension in patients with coronary artery disease

Abstract: Introduction: Coronary artery disease (CAD) remains the leading cause of mortality and morbidity worldwide, and hypertension is its most prevalent modifiable risk factor. Patients with CAD and concomitant hypertension are a special population with distinct physiologic and structural alterations. Optimal blood pressure (BP) control in this population has been linked with reduction in adverse outcomes, however, excessive lowering of BP could jeopardize myocardial and cerebral perfusion. Areas covered: Authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 69 publications
0
7
0
3
Order By: Relevance
“…Nos pacientes com evidência de isquemia miocárdica, a PAD deve ser reduzida com cautela até 70 mmHg, especialmente nos diabéticos e nos mais idosos. 312 Convém muito cuidado na redução da PAS nos idosos com DAC e com elevada pressão de pulso, pois isso pode resultar em valores muito baixos de PAD e propiciar isquemia miocárdica. 313…”
Section: O Hipertenso Com Doença Coronáriaunclassified
See 1 more Smart Citation
“…Nos pacientes com evidência de isquemia miocárdica, a PAD deve ser reduzida com cautela até 70 mmHg, especialmente nos diabéticos e nos mais idosos. 312 Convém muito cuidado na redução da PAS nos idosos com DAC e com elevada pressão de pulso, pois isso pode resultar em valores muito baixos de PAD e propiciar isquemia miocárdica. 313…”
Section: O Hipertenso Com Doença Coronáriaunclassified
“…In patients with evidence of myocardial ischemia, DBP should be cautiously lowered to 70 mm Hg, especially in diabetic patients and in the very old. 312 Lowering SBP in older patients with CAD and high pulse pressure requires great care, since they may lead to very low DBP values and trigger myocardial ischemia. 313…”
Section: 4 Hypertensive Patients With Coronary Diseasementioning
confidence: 99%
“…Guidelines recommend antianginal medications as the first line of treatment, with PCI performed for many patients who remain with persistent symptoms [ 3 , 4 ]. Many studies have shown that optimizing pharmacological therapy, lifestyle change, and education result in significant control of risk factors and consequently reduction in cardiovascular events [ 5 , 6 , 7 ]. Patients with moderate to severe symptoms and complex lesions who remain limited by angina, despite optimum medical therapy (OMT), are usually recommended for interventional treatment with the choice of the revascularization strategy determined by the coronary anatomy, individual’s comorbidities, and medical compliance [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Оскільки коморбідний перебіг ІХС з ГХ є однією з найбільш поширених кардіологічних проблем у сучасній клінічній практиці. Представляє інтерес визначення особливостей ремоделювання лівого шлуночка у пацієнтів з гіпертонічною хворобою при розвитку гострого інфаркту міокарда, це необхідно для стратифікації ризику розвитку можливих ускладнень ІХС і своєчасної їх корекції [9,10].…”
Section: особливості ремоделювання лівого шлуночка у пацієнтів з гіпеunclassified